Spatial structure supports diversity in prebiotic autocatalytic chemical ecosystems - Alex M. Plum; Christopher P. Kempes; Zhen Peng; David A. Baum (npj Complexity)
Abstract Autocatalysis is thought to have played an important role in the earliest stages of the origin of life. An autocatalytic cycle (AC) is a set of reactions that results in stoichiometric increase in its constituent chemicals. When the reactions of multiple interacting ACs are active in a region of space, they can have interactions analogous to those between species in biological ecosystems. Prior studies of autocatalytic chemical ecosystems (ACEs) have suggested avenues for accumulating complexity, such as ecological succession, as well as obstacles such as competitive exclusion. We extend this ecological framework to investigate the effects of surface adsorption, desorption, and diffusion on ACE ecology. Simulating ACEs as particle-based stochastic reaction-diffusion systems in spatial environments—including open, two-dimensional reaction-diffusion systems and adsorptive mineral surfaces—we demonstrate that spatial structure can enhance ACE diversity by (i) permitting otherwise mutually exclusive ACs to coexist and (ii) subjecting new AC traits to selection.